1987
DOI: 10.1073/pnas.84.7.1734
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transfer involving nonheme iron: the influence of leaving group ability on the rate constant for oxygen transfer to (EDTA)Fe(III) from peroxycarboxylic acids and hydroperoxides.

Abstract: Ethylenediaminetetraacetato iron (III) [ ( and zero-order reactions with the help of a computer program written for this purpose using a Hewlett-Packard Model 9825A computer. In the case of the alkyl hydroperoxide reactions, the oxygen transfer reactions were inconveniently slow and, therefore, the method of initial rates was employed to determine the rate constant from the absorbance vs. time kinetic trace for the oxygen transfer reactions as given (8, 9). Further, it should be noted that, since each equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Bruice's group has shown how the reactivity of [Fe 3+ (EDTA)(Sol)] -can be modulated by the identity of the "leaving group" of the oxygen atom donor. 784 A related phenomenon has also been observed with heme compounds, which catalyze oxygen transfer from OIC 6 F 5 faster than from OIPh. 772 Recently, the ability of a carboxylate-rich environment to support oxygen atom transfer chemistry in model systems was demonstrated.…”
Section: Reactivity Models Relevant To Monooxygenase Chemistrymentioning
confidence: 81%
See 1 more Smart Citation
“…Bruice's group has shown how the reactivity of [Fe 3+ (EDTA)(Sol)] -can be modulated by the identity of the "leaving group" of the oxygen atom donor. 784 A related phenomenon has also been observed with heme compounds, which catalyze oxygen transfer from OIC 6 F 5 faster than from OIPh. 772 Recently, the ability of a carboxylate-rich environment to support oxygen atom transfer chemistry in model systems was demonstrated.…”
Section: Reactivity Models Relevant To Monooxygenase Chemistrymentioning
confidence: 81%
“…In the wake of the crystal structure of the binuclear non-heme iron hydroxylase component of methane monooxygenase, which has a carboxylate-rich primary coordination sphere, the coordination chemistry of anionic ligands has returned to prominence in the modeling field. Bruice's group has shown how the reactivity of [Fe 3+ (EDTA)(Sol)] - can be modulated by the identity of the “leaving group” of the oxygen atom donor . A related phenomenon has also been observed with heme compounds, which catalyze oxygen transfer from OIC 6 F 5 faster than from OIPh …”
Section: Reactivity Models Relevant To Monooxygenase Chemistrymentioning
confidence: 99%
“…Linear free energy relationship (LFER) analyses have given insight into the kinetics and mechanisms of bond cleavage by oxidation catalysts. These analyses have shown that rate constants for RO–O(H) bond heterolysis ( k RO–O(H) ) depend linearly on the p K a of the leaving group (RO – + H + ⇆ ROH). , Leaving groups that are stronger acids (and hence relatively stable anions) are associated with faster heterolytic bond scission. As leaving group p K a ’s increase, however, the downward linear trend in k RO–O(H) values abruptly ceases and the plot becomes horizontal.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to radical chain reactions in ferric−peroxide systems, metal-based active oxygen species have been postulated (Scheme b). 1e,17e,,90b,c, In relation to the well-studied heme systems, , one could reasonably assume that such a species would be highly reactive toward organic substrates. However, a key question related to the existence of a high-valent iron-oxo intermediate in a mononuclear non-heme environment is the source of its stability.…”
Section: Discussionmentioning
confidence: 99%